Fabrication and Processing of Magnesium-Based Metal Matrix Nanocomposites for Bioabsorbable Implants - Andres Larraza; Shane Burke; Pedram Sotoudehbagha; Mehdi Razavi (Metals)
A novel magnesium (Mg)-based metal matrix nanocomposite (MMNC) was fabricated using ultrasonic melt treatment to promote the de-agglomeration of the bioactive glass–ceramic nanoparticles and the homogenization of the melt. The cast samples were then heat treated, machined, and hot rolled to reduce grain size and remove structural defects. Standard mechanical and electrochemical tests were conducted to determine the effect of fabrication and processing on the mechanical and corrosion properties of MMNCs. Compression tests, potentiodynamic polarization tests, electrochemical impedance spectroscopy, and static immersion testing were conducted to determine the characteristics of the MMNCs. The results showed that the combination of ultrasonic melt processing and thermomechanical processing caused the corrosion rate to increase from 8.7 mmpy after 10 days of immersion to 22.25 mmpy when compared with the ultrasonicated MMNCs but remained stable throughout the immersion time, showing no statistically significant change during the incubation periods. These samples also experienced increased yield stress (135.5 MPa) and decreased elongation at break (21.92%) due to the significant amount of grain refinement compared to the ultrasonicated MMNC (<semantics>σY</semantics> = 59.6 MPa, elongation = 40.44%). The MMNCs that underwent ultrasonic melt treatment also exhibited significant differences in the corrosion rate calculated from immersion tests.